Five essays in empirical finance - Pauls, Thomas; Justus Liebig University Giessen (My University, 2017)
This thesis consists of five independent research papers empirically addressing several questions relating to topics in "Analyst-Research", "Household Finance" and "Content-Analysis".The first paper elaborates on the herding/ anti-herding behavior of financial analysts.The second paper analyzes the role of narrow-scope and broad-scope trust in financial advice. The third paper analyzes the role of gender and financial literacy in households´ debt behavior.The fourth paper describes the adaptation of an English dictionary for content-analyses.The fifth paper analyzes the effect of textual sentiment in CEO speeches held at companies annual general meetings.

Diese Arbeit besteht aus fünf unabhängigen Forschungsarbeiten, die verschiedene Fragen zu Themen in "Analyst-Research", "Household Finance" und "Content-Analysis" empirisch behandeln.Das erste Papier beschreibt das Herding/Anti-herding Verhalten von Finanz-Analysten.Das zweite Papier analysiert die Rolle des broad-scope und narrow-scope Vertrauen in der Finanzberatung.Das dritte Papier analysiert die Rolle des Geschlechts und der Financial Literacy im Schuldenverhalten von Privathaushalten.Das vierte Papier beschreibt die Adaption eines englischen Wörterbuchs für Content-Analysen.Das fünfte Papier analysiert die Wirkung von Tonalität in CEO-Reden bei jährlichen Generalversammlungen.
Keywords: Household Finance; Content-Analyse; ddc:330